HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN KOPING KELUARGA DALAM MERAWAT PASIEN DI RUANG INTENSIVE CARE UNIT - Suprayitno Suprayitno; Sri Mumpuni Yuniarsih; Rahajeng Win Martani (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2020)
Family members treated in the ICU cause anxiety for the family. Anxiety is caused by many factors including the certainty of diagnosis, prognosis of the disease, financing and healing of patients. In dealing with anxiety every family has their own adaptation abilities, good adaptation will realize coping mechanisms that are good too. Family coping is influenced by several factors one of which is family social support. Objective: To find out the relationship between family social support and the coping of the family of patients treated in the ICU Room of the District Hospital of Batang. The research design used in this study is a correlative analytic cross sectional approach. The sample of the study was 30 families of patients treated in ICU room at Batang District Hospital with a total sampling technique. The instrument in this study was a questionnaire that was developed and tested for validity and reliability by researchers. Data analysis using chi square test. The results of the study: there is a relationship between family social support and family coping of patients treated in the ICU Room of Batang District Hospital with a ρ value of 0.001 <0.05. Suggestion: families should utilize positive coping sources around them to form adaptive coping mechanisms.